PERBEDAAN VARIASI PENAMBAHAN MEDIA ADSORPSI KONTAK AERASI SISTEM NAMPAN BERSUSUN (TRAY AERATOR) TERHADAP KADAR BESI (Fe) AIR SUMUR GALI DI DESA JATIHADI KECAMATAN SUMBER KABUPATEN REMBANG - Savitri Rachmawati; Tri Joko; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
People in the Jatihadi village are using dug wells water which contain high iron level. The average of iron level is 2,79 mg/l. Appropriate technology tray aerator with media contacts zeolite and activated carbon is the right solution to overcome the problems of high Fe content. This study aims to analyze the difference variation the addition of contact media adsorption on tray aerator for dug wells iron level in Jatihadi village, Sumber subdistrict, Rembang regency. The design of this study is pre experiment research with one group pretest posttest design.  We used Inductively Coupled Plasma (ICP) method to measure the iron level. Water sample volume for each aeration is 20 liters and there are 16 repetitions. The media that we used in this research is zeolite and activated carbon. The result showed average levels of iron before treatment is 2,79 mg/l, and after the first treatment down to 0,21 mg/l, after second treatment is 0,25 mg/l. Statistical analysis showed that there is no difference between variation of contact media adsorption for dug wells  iron level, but Wilcoxon analysis showed that there is a significant difference between before and after treatment for adding zeolite or activated carbon. The efficiency of tray aerator with the addition of zeolite is higher than addition of activated carbon.